Implication of Role Playing Techniques in Group Guidance to Address Bullying Issues among Students - Eni Rakhmawati; Faizin; Roikhatul Jannah; Akhmad Muzakki; Diah Ayu Lestari (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2026)
Bullying in schools is a socio-psychological problem that has a significant impact on the emotional, academic, and moral development of students. This phenomenon is still found at MA Al Iman Adiwerna, especially in the form of verbal bullying and mild physical violence, which are often considered jokes. This study aims to analyze the effectiveness of role-playing techniques in group guidance services to address bullying behavior among students in class X-1. The study uses a qualitative approach with a case study design, involving 11 participants consisting of the principal, guidance and counseling teachers, and students. Data collection was conducted through interviews, observations, and documentation, then analyzed using the Miles and Huberman model. The results showed that the application of role-playing techniques was effective in increasing students' awareness of the impact of bullying, improving interpersonal communication, and fostering empathy and emotional sensitivity. The experience of playing the roles of perpetrator, victim, and witness helped students understand the emotional and moral consequences of bullying behavior. These findings confirm that role-playing techniques are an effective and sustainable group guidance intervention strategy that contributes to strengthening character education and creating a safe and inclusive learning environment.